Incidence and factors associated with post-sternotomy pain syndrome in the National Heart Institute, Malaysia - Sudin, Arif; Chong, Collins; Hassan, Rozaini (Elsevier, 2024)
Objective: To determine the incidence of poststernotomy pain syndrome (PSPS) after open cardiac surgery in 2021. To determine characteristics and assess the severity of symptoms in patients diagnosed with PSPS. To identify factors that can be associated with patients who were positive for PSPS.